2016
DOI: 10.18632/oncotarget.7993
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 promotes cell proliferation in HBx-induced hepatocarcinogenesis as a critical transcription factor regulating lncRNAs

Abstract: The involvement of the hepatitis B virus X (HBx) protein in epigenetic modifications during hepatocarcinogenesis has been previously characterized. Long noncoding RNAs (lncRNAs), a kind of epigenetic regulator molecules, have also been shown to play crucial roles in HBx-related hepatocellular carcinoma (HCC). In this study, we analyzed the key transcription factors of aberrantly expressed lncRNAs in the livers of HBx transgenic mice by bioinformatics prediction, and found that ecotropic viral integration site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…WRN’s functions are related to its DNA helicase and exonuclease activities, and therefore, it interacts with p53 in DNA replication, repair, and recombination pathways to influence genomic instability[ 33 ]. The functions of MECOM in HCC carcinogenesis are linked with hepatitis B X protein carcinogenesis and antagonized growth inhibition induced by transforming growth factor-β (TGF-β) signaling[ 34 ]. Another CNA-linked gene, ELAC2 , encodes a protein that contributes to endoribonuclease activity for tRNA 3′ processing[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…WRN’s functions are related to its DNA helicase and exonuclease activities, and therefore, it interacts with p53 in DNA replication, repair, and recombination pathways to influence genomic instability[ 33 ]. The functions of MECOM in HCC carcinogenesis are linked with hepatitis B X protein carcinogenesis and antagonized growth inhibition induced by transforming growth factor-β (TGF-β) signaling[ 34 ]. Another CNA-linked gene, ELAC2 , encodes a protein that contributes to endoribonuclease activity for tRNA 3′ processing[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused on proteins that usually function as epigenetic regulators ( Table S7 ). MECOM, a member of the transcriptional regulator family, is of particular interest as it can contribute to the tumorigenesis of HCC 26 , 27 , and displays histone methyltransferase activity in the monomethylation of Lys9 of histone H3 (H3K9me1) in vitro 28 , 29 . Reciprocal co-immunoprecipitation experiments showed that MECOM specifically binds to DDX56 (Figure 7 A), while immunofluorescence experiments demonstrated that DDX56 and MECOM were colocalized in HCC cells (Figure 7 B).…”
Section: Resultsmentioning
confidence: 99%
“…Upregulated by HBx, WEE2-AS1 is able to accelerate the proliferation, migration, invasion and cell cycle progression of HCC cells through increasing the expression of Fermitin family member 3 (94). Additionally, recent studies have shown that the expression levels of lncRNAs are regulated by HBx (95)(96)(97)(98)(99).…”
Section: Dbh-as1 Dbh-as1mentioning
confidence: 99%